2023
DOI: 10.1021/acsaelm.2c01255
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and Electronic Structure of Oxygen Vacancy Stabilized Rhombohedral Hafnium Oxide

Abstract: Hafnium oxide is an outstanding candidate for next-generation nonvolatile memory solutions such as OxRAM (oxide-based resistive memory) and FeRAM (ferroelectric random access memory). A key parameter for OxRAM is the controlled oxygen deficiency in HfO2‑x which eventually is associated with structural changes. Here, we expand the view on the recently identified (semi-)conducting low-temperature pseudocubic phase of reduced hafnium oxide by further X-ray diffraction analysis and density functional theory (DFT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…The low fraction of the Ophase is suggested to be caused by both oxygen-rich conditions and the negative formation energy of neutral oxygen compared with the t-phase. 11,87 Nico et al 100 reported oxygen vacancyinduced phase transition from the monoclinic to rhombohedral phase (Fig. 11e).…”
Section: Oxygen Migration and Phase Transitionsmentioning
confidence: 97%
See 1 more Smart Citation
“…The low fraction of the Ophase is suggested to be caused by both oxygen-rich conditions and the negative formation energy of neutral oxygen compared with the t-phase. 11,87 Nico et al 100 reported oxygen vacancyinduced phase transition from the monoclinic to rhombohedral phase (Fig. 11e).…”
Section: Oxygen Migration and Phase Transitionsmentioning
confidence: 97%
“…High-angle annular dark-field (HAADF)-STEM analysis displayed a strong contrast associated with the heavy Hf atoms. Both the o-FE phases with a boundary along [100]/[001] o-FE can be directly observed, showing irregularly shaped ab and bc twin domains and a curved domain wall. 9 To better visually characterize both the crystal orientation and phase information with high spatial resolution (B2 nm), Lee et al 10 used a TEM precession electron diffraction (PED) technique for two-dimensional mapping (Fig.…”
Section: Orthorhombic Phasementioning
confidence: 99%
“…Monoclinic hafnia (P2 1 /c) 128 is the most stable phase under standard conditions 122 but transitions to a tetragonal (P4 2 / nmc) or cubic (Fm3̅ m) phase at higher temperatures. 129 Likewise, two distinct orthorhombic phases have been observed at high pressures (Pbca and Pnma), and both exhibit ferroelectric properties. 130 Hafnium sulfide is another significant nanomaterial owing to advantageous optoelectronic properties 43 and crystallizes in a hexagonal structure.…”
Section: Characterization and Morphologymentioning
confidence: 99%
“…Hafnium oxide, one of the most commonly studied chemical compositions for hafnium-based nanomaterials, may exhibit an amorphous nature or exist in four different crystal systems. Monoclinic hafnia ( P 2 1 / c ) is the most stable phase under standard conditions but transitions to a tetragonal ( P 4 2 / nmc ) or cubic ( Fm 3̅ m ) phase at higher temperatures . Likewise, two distinct orthorhombic phases have been observed at high pressures ( Pbca and Pnma ), and both exhibit ferroelectric properties .…”
Section: Characterization and Morphologymentioning
confidence: 99%
“…Recent works have shown the oxygen-vacancy binding energy in monoclinic HfO 2 , which is the difference between the formation energy of concurrently incorporating various oxygen vacancies and the coexistence energy of a single oxygen vacancy. [195,196] Another work demonstrated the development and analysis of a coincidence site lattice grain boundary configuration for cubic HfO 2 . [197,198] Additionally, the results of traditional computations reveal that oxygen vacancies at the HfO 2 grain boundary are insufficient to generate a metallic conductive channel.…”
Section: Origin Of Conductive Filament Formationmentioning
confidence: 99%